STUDI IN SILICO SENYAWA YANG TERKANDUNG DI DALAM RIMPANG TEMULAWAK (Curcuma xanthorriza Roxb.) SEBAGAI ANTIHEPATITIS B - Riska Prasetiawati; Shielva Meilanda; Benny Permana; Novriyanti Lubis (Jurnal Insan Farmasi Indonesia, 2021)
Hepatitis B is inflammation of the liver caused by the Hepatitis B virus (HBV). HBV is a DNA virus that plays a role in virus replication through the process of reverse transcription. The curcuma rhizome against HBV reseptor with protein ID 1A7L and ID 1IUD using the Autodock Tools program. The 1A7L receptor showed that the curcumin compound had ?G of -8.05 kcal/mol and the value of inhibition constant (KI) of 1.26 µM, natural ligands had ?G of -8.17 kcal/mol and the value of KI was 1.03 µM, and Lamivudin as a comparative ligand had ?G of -7.02 kcal/mol and the value of the KI was 7.13 µM, while the result of the 1IUD receptor had ?G of -8.44 kcal/mol and KI value of 647.75 nM, natural ligand had ?G of -6.90 kcal/mol and KI value of 8.78 µM, and Lamivudin as a comparative ligand had ?G of -5.01 kcal/mol and the value of the KI was 211.47 nM. The absorption and distribution prediction results showed the curcumin compound had a Caco2 value of 20.07 nm sec-1, the percentage of HIA was 94.40% and plasma Binding Protein was 88.03%. The curcumin compound fulfills all Lipinski's is non-mutagenic and carcinogenic negative.